Renin–Angiotensin–Aldosterone System Inhibitors and COVID-19 Infection or Hospitalization: A Cohort Study. (13th October 2020) - Dublin, Sascha; Walker, Rod L; Floyd, James S; Shortreed, Susan M; Fuller, Sharon; Albertson-Junkans, Ladia; Harrington, Laura B; Greenwood-Hickman, Mikael Anne; Green, Beverly B; Psaty, Bruce M
Abstract: Background: Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) may increase the risk of coronavirus disease 2019 (COVID-19) infection or affect disease severity. Prior studies have not examined risks by medication dose. Methods: This retrospective cohort study included people aged ≥18 years enrolled in a US integrated healthcare system for at least 4 months as of 2/29/2020. Current ACEI and ARB use was identified from pharmacy data, and the estimated daily dose was calculated and standardized across medications. COVID-19 infections and hospitalizations were identified through 6/14/2020 from laboratory and hospitalization data. We used logistic regression to estimate odds ratios (ORs) and 95% confidence intervals (CIs), adjusting for race/ethnicity, obesity, and other covariates. Results: Among 322, 044 individuals, 826 developed COVID-19 infection. Among people using ACEI/ARBs, 204/56, 105 developed COVID-19 (3.6 per 1, 000 individuals) compared with 622/265, 939 without ACEI/ARB use (2.3 per 1, 000), yielding an adjusted OR of 0.91 (95% CI 0.74–1.12). For use of <1 defined daily dose (DDD) vs. nonuse, the adjusted OR for infection was 0.92 (95% CI 0.66–1.28); for 1 to <2 DDDs, 0.89 (95% CI 0.66–1.19); and for ≥2 DDDs, 0.92 (95% CI 0.72–1.18). The OR was similar for ACEIs and ARBs and in subgroups by age and sex. 26% of people with COVID-19 infection were hospitalized; the adjusted OR for hospitalization in relation to ACEI/ARB use was 0.98 (95% CI 0.63–1.54), and there was no association with dose. Conclusions: These findings support current recommendations that individuals on these medications continue their use. Graphical Abstract: